Asset Specificity and Conservatism on Manufacturing Company in Indonesian - Furisanda, Muhammad Ferdian; Zubaidah, Siti; Irawan, Dwi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The purpose of this study is to provide empirical evidence regarding the effect of Asset Specificity on conservatism in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. Asset Specificity is an asset owned by a company that has its own characteristics that are not easily imitated by competitors. Assets that have certain characteristics are able to contribute to variations in conservative financial reporting practices. This study uses 210 data from manufacturing companies listed on the BEI, the sample was selected using the purposive sampling method for the period 2017-2019. The data of this research is in the form of panel data which is analyzed using a simple linear regression method which is processed using Stata15. The results of this study indicate that asset specificity has a negative effect on conservatism of manufacturing companies listed on the IDX in 2017-2019. The asset specificity owned by the company has not been able to make the company more conservative in preparing financial statements. Keywords: asset specificity, conservatism, IDX, Manufacturing companies